(untitled) (Research, Society and Development, 2022)
Flow is one of the essential process variables in distillation plants, and its constant measurement and control are necessary to achieve the best performance. This work aims to guarantee the process of automation, control, and calibration of a flow measurement instrument in an experimental distillation plant. A program was created in the Arduino IDE to determine the flowmeter coefficient, with a flow adjusted (manually) in the range of 0.3 L/min (indicated by the serial), measuring the actual flow rate with the aid of a 500 mL beaker, allowing the pre-defined flow rate to fill the beaker with the aid of a hose for 1 minute. With the coefficient defined for the meter (model YF-S401), five flows were chosen, starting at 0.25 L/min to 1.25 L/min. With the help of the IDE and Labview, a VI (Virtual Instrument) was created combining Labview/LINX with the help of the VISA (Virtual Instrument Software Architecture) tool. In both parts of the experiment, surface response (assisted by the STATISTICA 10 software) was used for the relationship between frequency, pulse, and flow. After the results obtained in the manual experiment and the automated experiment, the correlations obtained and the surface responses found to suggest an effective response of the integration of LINX and VISA for the measurement of flow, besides confirming the calibration (because the program corrects the error using the correlations). It is possible to state that the developed program can be integrated into a more complete automation system.